The Role of Relational Capital as a Dynamic Capability and Its Effect on the Relationship Between Directors’ Network and Firm Performance - Masduki, Saiful Bakhtiar; Saleh, Norman Mohd; Osman, Lokhman Hakim; Rahman, Mara Ridhuan Che Abdul; Keliwon, Kamarul Baraini (The South East Asian Journal of Management, 2026)
Research Aims: This study aims to examine how directors’ networks (DIRNET) improve firm performance and how relational capital (RELCAP) helps mediate this relationship in Malaysian public-listed firms. Design/Methodology/Approach: The adopted research design makes use of secondary data that involves 579 publicly listed firms within the period of 2017-2019. DIRNET and RELCAP measured through social network analysis techniques. Panel regression is applied to test the models and ensure robustness of the research findings. Research Findings: DIRNET is positively related to firm performance, and this effect is partially mediated by RELCAP, which positively influences performance. However, the relationship between DIRNET and firm performance is described by an inverted U-curve, which means that too many relationships among directors negatively contribute to performance advantages. Theoretical Contribution/Originality: The study finds that DIRNET value creation should go beyond traditional roles of governance. Further, it finds that too many director links can actually lower performance benefits. Finally, it adds new evidence from a relationship-based system of governance in an emerging economy. Managerial Implication in the South East Asian Context: In the South East Asian context, managers should assist directors in developing networks and good relationship with stakeholders. Stronger networks will enhance performance, but too many networks reduce performance gains. The valuation of networks and relationship helps firms to make good decisions, and utilise resources efficiently. Research Limitation & Implications: This study is limited to Malaysian publicly listed companies and annual report information, but it indicates the importance of developing a good network of directors to improve company performance, particularly boards in emerging market economies.